Episodic entrainment of deep primordial mantle material into ocean island basalts - Williams, Curtis D. (Nat Commun, 2015)
Chemical differences between mid-ocean ridge basalts (MORBs) and ocean island basalts (OIBs) provide critical evidence that the Earth's mantle is compositionally heterogeneous. MORBs generally exhibit a relatively low and narrow range of (3)He/(4)He ratios on a global scale, whereas OIBs display larger variability in both time and space. The primordial origin of (3)He in OIBs has motivated hypotheses that high (3)He/(4)He ratios are the product of mantle plumes sampling chemically distinct material, but do not account for lower MORB-like (3)He/(4)He ratios in OIBs, nor their observed spatial and temporal variability. Here we perform thermochemical convection calculations which show the variable (3)He/(4)He signature of OIBs can be reproduced by deep isolated mantle reservoirs of primordial material that are viscously entrained by thermal plumes. Entrainment is highly time-dependent, producing a wide range of (3)He/(4)He ratios similar to that observed in OIBs worldwide and indicate MORB-like (3)He/(4)He ratios in OIBs cannot be used to preclude deep mantle-sourced hotspots.